2011
DOI: 10.1111/j.1460-2466.2011.01582.x
|View full text |Cite
|
Sign up to set email alerts
|

The Choice Gap: The Divergent Online News Preferences of Journalists and Consumers

Abstract: This study examines 4 online news sites to compare stories that journalists display most prominently with stories consumers read most frequently. We find that journalists' chosen stories are “soft” with respect to subject matter but not story format, and that these choices diverge from consumers' choices, resulting in a choice gap. The study design makes important methodological contributions by using the story as the unit of analysis, operationalizing “soft news” in terms of subject matter as well as format, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
63
0
4

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(75 citation statements)
references
References 42 publications
3
63
0
4
Order By: Relevance
“…These findings about the independence from traffic concerns confirm what Gans (1979), and more recently Singer (2011) and Boczkowski and Peer (2011), have argued about newsrooms: that journalists choose what they think is news with little regard for what their audiences might want. Journalists reject quantitative information in favor of their own sense of what the audience ought to know, and feel good about being able to make editorial judgments.…”
Section: The Al Jazeera Difference: Web Metrics Without a Bottom Linesupporting
confidence: 88%
See 1 more Smart Citation
“…These findings about the independence from traffic concerns confirm what Gans (1979), and more recently Singer (2011) and Boczkowski and Peer (2011), have argued about newsrooms: that journalists choose what they think is news with little regard for what their audiences might want. Journalists reject quantitative information in favor of their own sense of what the audience ought to know, and feel good about being able to make editorial judgments.…”
Section: The Al Jazeera Difference: Web Metrics Without a Bottom Linesupporting
confidence: 88%
“…idea of public service (Zelizer 2005). Thus, journalists ignore the actual demands of audiences, choosing instead to prioritize their own news values (Boczkowski and Peer 2011;Singer 2011). Gans' (1979 classic newsroom ethnography offers a compelling account of how journalists selectively ignore audience feedback in their work: "Journalists have access to formal feedback for their work, but they use it only rarely" (230), and though "top producers and editors keep up with the ratings and circulation reports … they pay only cursory attention to the audience studies that come across their desk" (231).…”
Section: The Rise Of Web Metrics In Newsroomsmentioning
confidence: 99%
“…Boczkowski and Peer (2011), for example, found that journalists' "penchant" for public affairs news does not correlate with users' choices, as reflected in lists of popular items based on usage data, and that "consumers' preference for nonpublic affairs news might be less dependent on journalists' choices" (p. 867). Meanwhile, ongoing research into intermedia agenda setting effects among print and online sources remains inconclusive but continues to refine our understanding of their respective agendas (see Messner & Garrison, 2011;Maier, 2010;Weeks & Southwell, 2010;Messner & Distaso, 2008).…”
Section: Agenda-setting Theorymentioning
confidence: 99%
“…Emerging research already suggests the prominence of such material (Boczkowski & Peer, 2011;Barnhurst, 2013). Although the meatier stories published in print are likely to also appear online, they may or may not be foregrounded in the same way as the latest breaking news items that attract search engines, elicit user comment and drive traffic.…”
Section: A Word About Contentmentioning
confidence: 99%
“…Apoyando esta diversificación en el abordaje de los contenidos, diversos estudios han detectado cambios significativos en las prioridades informativas de las audiencias, así como una notable brecha entre la agenda propuesta por los medios y las noticias más leídas/vistas/escuchadas por el público. Algunos autores han encontrado que, salvo en momentos de máxi-ma tensión política, las audiencias tienden a demandar temáticas y tratamientos más soft en el periodismo político que los ofrecidos por los medios (Boczkowski y Peer, 2011).…”
Section: Introductionunclassified